The Relationship of Sleep Quality with Severity Level Acne Vulgaris in Students Aged 17-21 Years Faculty of Dentistry Prima Indonesia University - Rajagukguk, Marlina (Journal of Community Health Provision, 2024)
Acne vulgaris is chronic inflammation of the sebaceous glands. Many factors cause acne vulgaris, one of which is sleep quality. Poor sleep quality will cause an increase in androgen hormones which are associated with an increase in the incidence of acne vulgaris. Purpose: This study aims to determine the relationship between sleep quality and the severity of Acne vulgaris in students aged 17-21 years. This research is an analytical observational research with a cross-sectional method and sampling using a purposive sampling method. Research instruments using the Pittsburgh Sleep Quality Index (PSQI) questionnaire and the severity of acne vulgaris using the Lehmann classification. The result showed that of the 70 samples collected, there were 9 men and 61 women. There were 30 people with mild degree acne, 37 people with moderate degree and 3 people with severe degree. Based on sleep quality, there were 24 people with good sleep quality and 46 people with poor sleep quality. The results of Spearman's analytical correlation showed that there was a relationship between sleep quality and the severity of Acne vulgaris (P-value = 0.005). So, it can be concluded that sleep quality is related to the severity of Acne vulgaris in students aged 17-21 years.